MINAT CALON PEMILIK KARTU DEBIT DANAMON MANCHESTER UNITED DI YOGYAKARTA - Septi Anggraeni (Jurnal Riset Manajemen dan Bisnis, 2014)
The purpose of this study is to understanding the influence product, advertising design, advertising color, advertising message, and brand image toward interest to Danamon’s Debit Card Manchester United advertising brochure at Yogyakarta. The data was gained by spreading 100 questionnaires to 100 respondents who has never had the Danamon’s Debit Card Manchester United. The analysis methods that used in this research is multiple linear regressions. Based on the result of multiple linear regressions, the results showed product, brochure design, brochure color, brochure message and brand image that influencing the having interest of Danamon’s Debit Card Manchester United at Yogyakarta Keywords: Product, Brochure design, Brochure color, Brochure message and Brand image